Atomic layer deposition coating for high temperature ceramic component
Atomic layer deposition of rare earth metal-containing ceramics addresses the challenge of providing conformal and uniform coatings on complex chamber components, enhancing plasma resistance and maintaining performance in high-temperature environments.
Patent Information
- Application Number
- JP2024175435
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-12-06
- Filing Date
- 2024-10-07
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2039-12-04
AI Technical Summary
Existing methods for coating chamber components in semiconductor manufacturing, such as thermal spraying, sputtering, and plasma spraying, fail to provide conformal and uniform coatings on complex structural features, leading to design constraints and performance issues, especially for high-temperature heaters, and are not suitable for coating without significantly impacting heater performance.
Atomic layer deposition (ALD) techniques are used to apply rare earth metal-containing ceramic coatings, such as Y2O3, YZrO, YZrOF, Y3Al5O12, Y4Al2O9, YF3, YxOyFz, Er2O3, Er3Al5O12, ErF3, La2O3, Lu2O3, Sc2O3, ScF3, ScOF, Gd2O3, Sm2O3, Dy2O3, and their combinations, which are conformal, uniform, and non-porous, allowing for coatings on complex geometries and reducing plasma erosion.
ALD coatings maintain the thermal and electrical properties of high-temperature components, provide plasma resistance, and reduce material volatility, minimizing defects and maintaining component functionality.
Smart Images

Figure 2025004142000001_ABST
Abstract
Description
[Technical field]
[0001] Embodiments of the present disclosure relate to articles, coated chamber components, and methods of coating chamber components with ceramic coatings. The ceramic coating may include a rare earth metal-containing layer that coats all surfaces of a component (e.g., a high temperature heater or an electrostatic chuck). The ceramic coating may be formed using non-line-of-sight techniques such as atomic layer deposition (ALD). Background
[0002] Various semiconductor manufacturing processes use high temperatures, high energy plasmas, corrosive gas mixtures, high stresses, and combinations thereof. These extreme conditions often erode chamber components and generate particulate contaminants.
[0003] Typically, protective coatings are deposited on chamber components by a variety of methods, including thermal spraying, sputtering, plasma spraying, or vapor deposition techniques. These techniques generally cannot deposit conformal, uniform coatings on the complex structural features of the components, which imposes design constraints on the geometric complexity of such components. Furthermore, these techniques are generally not suitable for coating heater components without significantly affecting heater performance, as relatively thick coatings are used to provide the same level of heater protection as thinner, less defect-dense films. Summary of the Invention
[0004] Embodiments herein describe atomic layer deposition coatings for high temperature articles. In one aspect, the coated article comprises an article suitable for use in a processing chamber, the article comprising an exterior surface and an interior channel including an interior surface that is difficult to reach for line-of-sight deposition processing. The coated article further comprises a coating formed on the exterior and interior surfaces of the article, the coating comprising a rare earth metal-containing ceramic, the rare earth metal-containing ceramic being selected from the group consisting of Y2O3, YZrO, Y x Zr y O z , YZrOF, Y3Al5O 12 , Y4Al2O9, YF3, Y x O y F z , YOF, Er2O3, Er3Al5O 12 , ErF3, E x O y F z , ErOF, La2O3, Lu2O3, Sc2O3, ScF3, ScOF, Gd2O3, Sm2O3, Dy2O3, and combinations thereof. In some embodiments, the coating is substantially uniform, conformal, and non-porous.
[0005] In another aspect, a coated article comprises an article suitable for use in a processing chamber, an amorphous carbon adhesion layer formed on the article, and a coating formed on the amorphous carbon adhesion layer, the coating comprising a rare earth metal-containing ceramic, the rare earth metal-containing ceramic being selected from the group consisting of Y2O3, YZrO, Y x Zr y O z , YZrOF, Y3Al5O 12 , Y4Al2O9, YF3, Y x O y F z , YOF, Er2O3, Er3Al5O 12 , ErF3, E x O y F z, ErOF, La2O3, Lu2O3, Sc2O3, ScF3, ScOF, Gd2O3, Sm2O3, Dy2O3, and combinations thereof. In some embodiments, the coating is substantially uniform, conformal, and non-porous.
[0006] In another aspect, a method of forming a coated article includes providing an article suitable for use in a processing chamber, the article having a first coefficient of thermal expansion; selecting a molar ratio of the first rare earth metal-containing ceramic compound to a second rare earth metal-containing ceramic compound, such that a ceramic coating comprising the first and second rare earth metal-containing ceramic compounds in the selected molar ratio, when deposited on a surface of the article by atomic layer deposition, results in a ceramic coating having a second coefficient of thermal expansion, the second coefficient of thermal expansion being within 10% of the first coefficient of thermal expansion; and performing atomic layer deposition to deposit the ceramic coating on the surface of the article. [Brief description of the drawings]
[0007] The present disclosure is illustrated by way of example, and not by way of limitation, in the figures of the accompanying drawings and in which like reference symbols refer to similar elements. [Figure 1] A cross-sectional view of a processing chamber is shown. [Figure 2A] 1 illustrates one embodiment of a deposition process according to the atomic layer deposition technique described herein. [Figure 2B] 1 illustrates another embodiment of a deposition process according to the atomic layer deposition technique described herein. [Figure 2C] 1 illustrates another embodiment of a deposition process according to the atomic layer deposition technique described herein. [Diagram 3] 1 illustrates an exemplary susceptor having a ceramic coating formed thereon, according to various embodiments. [Figure 4] 1 illustrates an exemplary heater assembly having a ceramic coating formed thereon, according to various embodiments. [Diagram 5] 1 illustrates a cross-sectional side view of an exemplary component having an internal channel formed therein, according to embodiments. [Figure 6A] 1 illustrates a cross-sectional view of a surface of a component having a single layer formed thereon, according to embodiments. [Figure 6B] 1 illustrates a cross-sectional view of a surface of a component having multiple layers formed thereon, according to embodiments. [Figure 7] 1 illustrates a method of forming a ceramic coating using atomic layer deposition, according to various embodiments. [Figure 8] 1 is a transmission electron microscope photograph of a graphite substrate having an adhesion layer and a ceramic layer formed thereon, according to various embodiments. Detailed Description
[0008] The embodiments described herein address coated articles and methods by which coatings are deposited on articles. The coating may be a rare earth metal-containing layer (e.g., an yttrium-containing oxide layer or an yttrium-containing fluoride layer). Alternatively, the coating may be a multi-layer coating including one or more adhesion layers and one or more ceramic layers. The deposition process may be a non-line-of-sight process, such as an atomic layer deposition (ALD) process.
[0009] Existing ceramic heaters and coating methods have several drawbacks. For example, sputter yields and erosion rates are typically high when the heater is exposed to plasma, and especially when the heater is made of bulk ceramic AlN, Al2O3, or SiC coated graphite. For example, SiC and TaC coated graphite heaters are not compatible with fluorine-containing chemistries. Plasma spray and SiC coated graphite heaters are not conformal; therefore, their geometric complexity imposes design constraints. Also, it is difficult to tailor the coefficient of thermal expansion (CTE) of existing heater coatings, limiting their application to substrates with different CTEs at high temperatures. Most heater coatings are thick coatings which exacerbate this CTE mismatch problem.
[0010] The embodiments of the present disclosure address some of the problems of existing heater technology. For example, advantages of the embodiments of the present disclosure include the ability of rare earth oxide and oxyfluoride ALD coatings to provide conformal coverage to heaters, electrostatic chucks, and other complex shaped components that contain intricate, high aspect ratio internal features that cannot be reached by line-of-sight deposition techniques. Additionally, heaters with rare earth oxide and oxyfluoride ALD coatings exhibit low sputter yields under high energy plasma bombardment and are highly resistant to degradation from chemical / radical (e.g., from NF3 radical) attack. Heaters with rare earth oxide and oxyfluoride ALD coatings can also withstand (e.g., be exposed to without damage) higher temperatures compared to other coating techniques, which utilize much thicker coatings and thus generate higher stresses when there is a CTE mismatch. Heaters with rare earth oxide and oxyfluoride ALD coatings also naturally exhibit very high oxidation resistance. Additionally, ALD coatings have the advantage that, in embodiments, improved protection is possible by adjusting the ratios of different constituent materials (e.g., molar ratios of two or more metals) within the ALD coating to match the coating CTE to the CTE of various substrates.
[0011] The heater may be formed from aluminum nitride (AlN) material or other suitable material with comparable chemical resistance and mechanical, thermal, and electrical properties. Wires (e.g., tungsten wires) may be embedded in the heater material to provide electricity. In various embodiments, the heater material may be AlN ceramic, silicon carbide (SiC) ceramic, aluminum oxide (Al2O3) ceramic, graphite, or any combination thereof. Different heater materials have different reaction characteristics, and one composition may form a reactant with a higher vapor pressure than another composition when exposed to high temperature, low vacuum pressure, and aggressive chemical action. For example, when a typical high temperature heater with AlN material ceramic is exposed to nitrogen trifluoride (NF3) plasma under high temperature (e.g., up to about 650°C) and vacuum (e.g., about 50 mTorr to about 200 mTorr) conditions, the reaction produces aluminum trifluoride (AlF3). The vapor pressure of this aluminum trifluoride is approximately log(p / kpa)=11.70-14950(T / K). Therefore, AlF3 can sublime and deposit on other components in the chamber. During subsequent processing steps, the deposited material can flake, delaminate, or otherwise detach from other chamber components and deposit as particles on existing wafers, causing defects.
[0012] ALD allows for controlled, self-limiting deposition of material by chemical reaction with the surface of the article. In addition to being a conformal process, ALD is also a uniform process and can form very thin films, for example, having a thickness of about 3 nm or more. All exposed surfaces of the article have the same or nearly the same amount of material deposited. As described herein, the heater can have the same or substantially the same thermal conductivity and heating capacity as an uncoated heater. A typical reaction cycle of an ALD process begins with a precursor (i.e., a single chemical, A) flowing into the ALD chamber and adsorbing onto the surface of the article (including the surface of the pore walls within the article). After the excess precursor is pumped out of the ALD chamber, a reactant (i.e., a single chemical, R) is introduced into the ALD chamber and subsequently pumped out. With ALD, the final thickness of the material depends on the number of reaction cycles performed, since each reaction cycle grows a layer of a certain thickness, which may be an atomic layer or a fraction of an atomic layer.
[0013] ALD techniques can deposit thin layers of material at relatively low temperatures (e.g., about 25° C. to about 350° C.) and therefore do not damage or deform any of the material of the component. In addition, ALD techniques can also deposit layers of material within complex features (e.g., high aspect ratio features) of the component. Furthermore, ALD techniques generally produce relatively thin (i.e., 1 μm or less) coatings that are non-porous (i.e., pinhole-free), which can eliminate crack formation during deposition.
[0014] FIG. 1 is a cross-sectional view of a semiconductor processing chamber 100 having one or more chamber components coated with a coating layer, according to embodiments. The base material of the processing chamber 100 may include one or more of aluminum (Al), titanium (Ti), and stainless steel (SST). The processing chamber 100 may be used for processes in which a corrosive plasma environment having plasma processing conditions is provided. For example, the processing chamber 100 may be a chamber for a plasma etcher or plasma etch reactor, a plasma cleaner, a plasma enhanced chemical vapor deposition (CVD) or ALD reactor, and the like. Examples of chamber components that may be provided with a coating layer (e.g., a ceramic coating) include a substrate support assembly 148, an electrostatic chuck (ESC) assembly 150, a ring (e.g., a process kit ring or a single ring), a chamber wall, a base, a gas distribution plate, a showerhead, a liner, a liner kit, a shield, a plasma screen, a flow equalizer, a cooling base, a chamber viewport, a chamber lid, and the like. Various techniques may be used to deposit the coating on the components. Examples include ALD, sputtering, ion-assisted deposition, plasma spray coating, CVD, or other suitable techniques as would be understood by one of ordinary skill in the art. As shown, according to one embodiment, the substrate support assembly 148 has a ceramic coating layer 136. However, it should be understood that any of the other chamber components, such as those listed above, may also be provided with a coating layer.
[0015] Another example of a chamber component that may include a coating is the high temperature heater assembly. In some embodiments, the coating, described in more detail below, is applied by ALD. ALD allows for the application of conformal coatings of substantially uniform thickness, which are pore-free, on all types of components with complex shapes and high aspect ratio features.
[0016] In some embodiments, ALD may be used with a rare earth metal-containing precursor and a reactant consisting of or including oxygen, fluorine, or nitrogen to grow or deposit a coating that includes a rare earth metal. The rare earth metal-containing precursor may include yttrium, erbium, lanthanum, lutetium, scandium, gadolinium, samarium, or dysprosium. To additionally or alternatively grow or deposit a coating, ALD may be used with a precursor that deposits an adhesion layer having the same or similar material as the underlying component material to be deposited. For example, an aluminum-containing precursor and a nitrogen-containing reactant may be used to form AlN, or an aluminum-containing precursor and an oxygen-containing reactant may be used to form aluminum oxide (Al2O3). ALD may be used with one or more precursors that include a rare earth metal to grow or deposit a stack layer or wear-resistant layer on the adhesion layer. In some embodiments, sputtering, ion-assisted deposition, plasma spray coating, or CVD may be used to deposit the wear-resistant layer. The stack layers may have alternating thin layers of a rare earth metal-containing material and another oxide, fluoride or nitride material (such as Al2O3, AlN, Y2O3, YF3, etc.).
[0017] In one embodiment, the rare earth metal-containing layer has a polycrystalline structure. In another embodiment, the rare earth metal-containing layer may have an amorphous structure. The rare earth metal-containing layer may include yttrium, erbium, lanthanum, lutetium, scandium, gadolinium, samarium, and / or dysprosium. For example, the rare earth metal-containing layer may include yttrium (YO), yttrium fluoride (YF), yttrium oxyfluoride (YF ... x O y F z ), yttrium zirconium oxide (YZrO), erbium oxide (Er2O3), erbium fluoride (ErF3), erbium oxyfluoride (Er x O y F z ), erbium aluminum oxide (Er3Al5O 12), dysprosium oxide (Dy2O3), dysprosium fluoride (DyF3), dysprosium oxyfluoride (Dy x O y F z ), gadolinium oxide (Gd2O3), gadolinium fluoride (GdF3), gadolinium oxyfluoride (Gd x O y F z ), scandium oxide (Sc2O3), scandium fluoride (ScF3), scandium oxyfluoride (ScOF), etc. In various embodiments, the rare earth metal layer may include polycrystalline Y2O3, YF3, or Y x O y F z In other embodiments, the rare earth metal layer is amorphous Y2O3, YF3, or Y x O y F z In one embodiment, the rare earth metal-containing material may be co-deposited with another material. For example, the rare earth metal-containing oxide may be mixed with one or more other rare earth compounds, such as Y2O3, gadolinium oxide (Gd2O3), and / or erbium (e.g., Er2O3). The yttrium-containing oxide for the coating may be co-deposited with, for example, Y x Dy y O z , Y x Gd y O z Or Y x Er y O z The yttrium-containing oxide may be Y2O3 having a cubic structure in space group Ia-3(206). The subscripts x, y, and z may independently range from 0.1 to 10, for example.
[0018] In one embodiment, the rare earth metal-containing layer is Y2O3, Y x Zr y O z , YZrOF, Y3Al5O 12 (YAG), Y4Al2O9(YAM), YF3, Y x O y F z , Er2O3, Er3Al5O 12(EAG), ErF3, Er x O y F z , La2O3, Lu2O3, Sc2O3, ScF3, Sc x O y F z , Gd2O3, Sm2O3Dy2O3, or Nd2O3. The rare earth metal-containing layer is one of YAlO3 (YAP), Er4Al2O9 (EAM), ErAlO3 (EAP), Gd4Al2O9, GdAlO3, Nd3Al5O 12 , Nd4Al2O9, NdAlO3, a ceramic compound consisting of a solid solution of Y4Al2O9 and Y2O3-ZrO2, or other coating compositions described herein, as well as ternary variations of lanthanum, lutetium, scandium, gadolinium, samarium, or dysprosium, or other rare earth metal-containing compounds discussed herein. Any of the foregoing rare earth metal-containing materials may contain trace amounts of other materials, such as ZrO2, Al2O3, SiO2, B2O3, Er2O3, Nd2O3, Nb2O5, CeO2, Sm2O3, Yb2O3, or other oxides.
[0019] In some embodiments, the rare earth metal-containing layer includes Y2O3, ZrO2, and / or Al2O3 in amounts selected from the following compositions: Y2O3 in the range of 50-75 mol%, ZrO2 in the range of 10-30 mol%, and Al2O3 in the range of 10-30 mol%, or Y2O3 in the range of 40-99 mol%, ZrO2 in the range of 1-60 mol%, and Al2O3 in the range of 0-10 mol%, or Y2O3 in the range of 60-75 mol%, ZrO2 in the range of 20-30 mol%, and Al2O3 in the range of 0-5 mol%, or Y2O3 in the range of 60-70 mol%, ZrO2 in the range of 30-40 mol%, and Al2O3 in the range of 0-10 mol%, or or Al2O3 in the range of 50-60mol%, Y2O3 in the range of 50-60mol%, and ZrO2 in the range of 40-50mol%, or Y2O3 in the range of 40-60mol%, ZrO2 in the range of 30-50mol%, and Al2O3 in the range of 10-20mol%, or Y2O3 in the range of 40-50mol%, ZrO2 in the range of 20-40mol%, and Al2O3 in the range of 20-40mol%, or Y2O3 in the range of 70-90mol%, ZrO2 in the range of 0-20mol%, and Al2O3 in the range of 10-20mol%. or Y2O3 in the range of 60-80mol%, ZrO2 in the range of 0-10mol%, and Al2O3 in the range of 20-40mol%, or Y2O3 in the range of 40-60mol%, ZrO2 in the range of 0-20mol%, and Al2O3 in the range of 30-40mol%, or Y2O3 in the range of 30-60mol%, ZrO2 in the range of 0-20mol%, and Al2O3 in the range of 30-60mol%, or Y2O3 in the range of 20-40mol%, ZrO2 in the range of 20-80mol%, and 0-60mol%. 1% range of Al2O3, or 0-10mol% range of Y2O3, 20-30mol% range of ZrO2, and 50-60mol% range of Al2O3, or 0-10mol% range of Y2O3, 20-30mol% range of ZrO2, and 40-50mol% range of Al2O3, or 0-10mol% range of Y2O3, 10-20mol% range of ZrO2, and 50-60mol% range of Al2O3, or 0-10mol% range of Y2O3, 10-20mol% range of ZrO2,and Al2O3 in the range of 40-50 mol%, or Y2O3 in the range of 10-20 mol%, ZrO2 in the range of 20-30 mol%, and Al2O3 in the range of 50-60 mol%, or Y2O3 in the range of 10-20 mol%, ZrO2 in the range of 20-30 mol%, and Al2O3 in the range of 40-50 mol%, or Y2O3 in the range of 10-20 mol%, ZrO2 in the range of 50- 60mol% Al2O3, 10-20mol% Y2O3, 10-20mol% ZrO2, and 40-50mol% Al2O3, 0-10mol% Y2O3, 40-50mol% ZrO2, and 10-20mol% Al2O3, 0-10mol% Y2O3, 40-50mol% ZrO2, and 20-30mol% or 0-10 mol% Y2O3, 50-60 mol% ZrO2, and 10-20 mol% Al2O3; or 0-10 mol% Y2O3, 50-60 mol% ZrO2, and 20-30 mol% Al2O3; or 10-20 mol% Y2O3, 40-50 mol% ZrO2, and 10-20 mol% Al2O3. or 10-20 mol% Y2O3, 40-50 mol% ZrO2, and 20-30 mol% Al2O3; or 10-20 mol% Y2O3, 50-60 mol% ZrO2, and 10-20 mol% Al2O3; or 10-20 mol% Y2O3, or 50-60 mol% ZrO2, and 20-30 mol% Al2O3.
[0020] In some embodiments, the rare earth metal-containing layer includes Y2O3 and ZrO2 in amounts selected from the following compositions: Y2O3 in the range of 1-99 mol% and ZrO2 in the range of 1-99 mol%, or Y2O3 in the range of 1-50 mol% and ZrO2 in the range of 50-99 mol%, or Y2O3 in the range of 50-99 mol% and ZrO2 in the range of 1-50 mol%, or Y2O3 in the range of 50-75 mol% and ZrO2 in the range of 25-50 mol%, or Y2O3 in the range of 40-61 mol%, and 39-60 mol% ZrO2, or 65-99 mol% Y2O3 and 1-35 mol% ZrO2, or 65-80 mol% Y2O3 and 20-35 mol% ZrO2, or 60-70 mol% Y2O3 and 30-40 mol% ZrO2, or 1-11 mol% Y2O3 and 89-99 mol% ZrO2. or 11-21 mol% Y2O3 and 79-89 mol% ZrO2, or 21-31 mol% Y2O3 and 69-79 mol% ZrO2, or 31-41 mol% Y2O3 and 59-69 mol% ZrO2, or 41-51 mol% Y2O3 and 49-59 mol% ZrO2, or 51-61 mol% Y2O 3, and ZrO2 in the range of 39-49 mol%, or Y2O3 in the range of 61-71 mol%, and ZrO2 in the range of 29-39 mol%, or Y2O3 in the range of 71-81 mol%, and YF3 in the range of 19-29 mol%, or Y2O3 in the range of 81-91 mol%, and YF3 in the range of 9-19 mol%, or Y2O3 in the range of 91-99 mol%, and YF3 in the range of 1-9 mol%.
[0021] In some embodiments, the rare earth metal-containing layer includes Y2O3, ZrO2, Er2O3, Gd2O3, and / or SiO2 in amounts selected from the following compositions: Y2O3 in the range of 40-45 mol%, ZrO2 in the range of 0-10 mol%, Er2O3 in the range of 35-40 mol%, Gd2O3 in the range of 5-10 mol%, and SiO2 in the range of 5-15 mol%, or Y2O3 in the range of 30-60 mol%, ZrO2 in the range of 0-20 mol%, Er2O3 in the range of 20-50 mol%, Gd2O3 in the range of 0-10 mol%, and SiO2 in the range of 0-30 mol%, or Y2O3 in the range of 30-45 mol%, ZrO2 in the range of 5-15 mol%, Er2O3 in the range of 25-60 mol%, and Gd2O3 in the range of 0-25 mol%.
[0022] In some embodiments, the rare earth metal-containing layer includes Y2O3 and YF3 in amounts selected from the following compositions: Y2O3 in the range of 1-99 mol% and YF3 in the range of 1-99 mol%, or Y2O3 in the range of 1-10 mol% and YF3 in the range of 90-99 mol%, or Y2O3 in the range of 11-20 mol% and YF3 in the range of 80-89 mol%, or Y2O3 in the range of 21-30 mol% and YF3 in the range of 70-79 mol%, or Y2O3 in the range of 31-40 mol% and YF3 in the range of 60-69 mol%, or Y2O3 in the range of 41-50 mol%, and YF3 in the range of 50 to 59 mol%, or Y2O3 in the range of 51 to 60 mol%, and YF3 in the range of 40 to 49 mol%, or Y2O3 in the range of 61 to 70 mol%, and YF3 in the range of 30 to 39 mol%, or Y2O3 in the range of 71 to 80 mol%, and YF3 in the range of 20 to 29 mol%, or Y2O3 in the range of 81 to 90 mol%, and YF3 in the range of 10 to 19 mol%, or Y2O3 in the range of 91 to 99 mol%, and YF3 in the range of 1 to 9 mol%.
[0023] It should be understood that the foregoing ranges are exemplary and that there may be some variation in the limits for each compound. For example, when "YO3 in the range of 41-50 mol%" is stated, it is understood to include all possible amounts of YO3 from above 41 mol% to below 50 mol%, and from about 41 mol% to about 50 mol%, taking into account approximations and measurement uncertainties.
[0024] Referring again to FIG. 1 , in one embodiment, the processing chamber 100 includes a chamber body 102 and a showerhead 130, which surround an interior volume 106. The showerhead 130 may comprise a showerhead base and a showerhead gas distribution plate. Alternatively, the showerhead 130 may be replaced by a lid and a nozzle in some embodiments, or by a plurality of fan-shaped showerhead sections and a plasma generating unit in other embodiments. The chamber body 102 may be fabricated from other suitable materials, such as aluminum, stainless steel, or titanium. The chamber body 102 generally includes a sidewall 108 and a bottom 110. One or more of the showerhead 130 (or the lid and / or the nozzle), the sidewall 108, and / or the bottom 110 may comprise a coating layer.
[0025] An outer liner 116 may be disposed adjacent the sidewall 108 to protect the chamber body 102. The outer liner 116 may be fabricated and / or coated with a coating layer. In one embodiment, the outer liner 116 is fabricated from aluminum oxide.
[0026] An exhaust port 126 may be defined in the chamber body 102 and may connect the interior volume 106 to a pumping system 128. The pumping system 128 may include one or more pumps and a throttle valve and may be utilized to evacuate and regulate the pressure of the interior volume 106 of the processing chamber 100.
[0027] The showerhead 130 may be supported on the sidewall 108 of the chamber body 102. The showerhead 130 (or lid) may be open to allow access to the interior volume 106 of the processing chamber 100 or may be closed to provide an airtight seal to the processing chamber 100. A gas panel 158 may be connected to the processing chamber 100 to supply process and / or cleaning gases to the interior volume 106 through the showerhead 130 or the lid and nozzles. The showerhead 130 may be used in processing chambers used for dielectric etching (etching dielectric materials). The showerhead 130 comprises a gas distribution plate (GDP) 133 having a plurality of gas supply holes 132 throughout. The showerhead 130 may comprise a GDP 133 bonded to an aluminum or anodized aluminum showerhead base 104. The GDP 133 may be made of Si or SiC or may be a ceramic such as Y2O3, Al2O3, YAG, etc.
[0028] For processing chambers used for conductor etching (etching conductive materials), a lid may be used rather than a showerhead. The lid may include a central nozzle that fits into the central hole of the lid. The lid may be ceramic, such as Al2O3, Y2O3, YAG, or a ceramic compound of Y4Al2O9 and a solid solution of Y2O3-ZrO2. The nozzle may also be ceramic, such as Y2O3, YAG, or a ceramic compound of Y4Al2O9 and a solid solution of Y2O3-ZrO2. Optionally, the lid, showerhead base 104, GDP 133, and / or nozzle may be coated with a ceramic coating.
[0029] Examples of process gases that may be used to process a substrate in the process chamber 100 include halogen-containing gases (such as C2F6, SF6, SiCl4, HBr, NF3, CF4, CHF3, CH2F3, F, NF3, Cl2, CCl4, BCl3, and SiF4, among others), as well as gases such as O2 or N2O. The coating layer may be resistant to erosion by some or all of these gases and / or by plasma generated from these gases. Examples of carrier gases include N2, He, Ar, and other gases that are inert to the process gases (e.g., non-reactive gases).
[0030] The substrate support assembly 148 is disposed in the interior volume 106 of the processing chamber 100 below the showerhead 130 or lid. The substrate support assembly 148 holds the substrate 144 during processing. A ring 146 (e.g., a single ring) may cover a portion of the ESC assembly 150 to protect the covered portion from exposure to plasma during processing. In one embodiment, the ring 146 may be silicon or quartz.
[0031] An inner liner 118 may be coated around the substrate support assembly 148. The inner liner 118 may be a halogen-containing gas resistant material (such as those materials mentioned with respect to the outer liner 116). In one embodiment, the inner liner 118 may be fabricated from the same material as the outer liner 116. Additionally, the inner liner 118 may be coated with a ceramic coating.
[0032] In one embodiment, the substrate support assembly 148 comprises a mounting plate 162 supporting the pedestal 152, and an ESC assembly 150. The ESC assembly 150 further comprises a thermally conductive base 164 and an electrostatic puck 166 adhered to the thermally conductive base by an adhesive 138. In one embodiment, the adhesive may be a silicone adhesive. The top surface of the electrostatic puck 166 is covered by a ceramic coating layer 136 in the illustrated embodiment. In one embodiment, the ceramic coating layer 136 is disposed on the top surface of the electrostatic puck 166. In another embodiment, the ceramic coating layer 136 is disposed on the entire exposed surface of the ESC assembly 150. This exposed surface includes the exterior and side periphery of the thermally conductive base 164 and the electrostatic puck 166. The mounting plate 162 is coupled to the bottom 110 of the chamber body 102 and comprises passages for routing utilities (e.g., fluids, power lines, sensor leads, etc.) to the thermally conductive base 164 and the electrostatic puck 166.
[0033] The thermally conductive base 164 and / or the electrostatic puck 166 may include one or more optional embedded heating elements 176, embedded insulation 174, and / or conduits 168, 170 to control the lateral temperature profile of the substrate support assembly 148. The conduits 168, 170 are fluidly connected to a fluid source 172, which may circulate a temperature regulating fluid through the conduits 168, 170. The embedded insulation 174 may be disposed between the conduits 168, 170 in one embodiment. The heating element 176 is regulated by a heater power supply 178. The conduits 168, 170 and the heating element 176 may be utilized to control the temperature of the thermally conductive base 164, which may in turn heat and / or cool the electrostatic puck 166 and the substrate (e.g., wafer) 144 being processed. The temperatures of the electrostatic puck 166 and the thermally conductive base 164 may be monitored using a number of temperature sensors 190, 192. A controller 195 may be used to monitor these multiple temperature sensors.
[0034] The electrostatic puck 166 may further include a number of gas passages, such as grooves, mesas, and other surface features. These gas passages may be formed in the puck 166 and / or the top surface of the ceramic coating layer 136. The gas passages may be fluidly connected to a source of heat transfer (or backside) gas, such as helium, through holes drilled in the puck 166. During operation, a backside gas may be supplied to the gas passages at a controlled pressure to enhance heat transfer between the electrostatic puck 166 and the substrate 144. The electrostatic puck 166 includes at least one clamping electrode 180 controlled by a chucking power supply 182. The electrode 180 (or other electrodes disposed on the puck 166 or base 164) may be further connected to one or more radio frequency power supplies 184, 186 through a matching network 188 to maintain a plasma formed from the process gas and / or other gases in the processing chamber 100. The power sources 184, 186 are generally capable of generating radio frequency signals having frequencies from about 50 kHz to about 3 GHz and having a power output of up to about 10,000 Watts.
[0035] ALD techniques enable conformal coatings of relatively uniform thickness and zero porosity (i.e., non-porous) on surfaces of chamber components and on features with complex geometries, including interior geometries that cannot be reached by conventional line-of-sight deposition techniques. The coatings are plasma resistant and can reduce plasma interaction without affecting performance, improving component durability. Thin coatings deposited with ALD can maintain the electrical properties and relative shape and geometric configuration of the component so as not to interfere with its function. The coatings can also reduce the volatility of the component material, forming reactants with lower vapor pressures than the component's underlying material.
[0036] The resistance of a coating to plasma may be measured by its "etch rate" (ER). The units of this etch rate are micrometers / hour (μm / hr) or angstroms / hour (Å / hr). The measurement period is the entire period during which the coated component is in operation and exposed to the plasma. The treatment time before the measurement may vary. For example, the measurement is performed before treatment, or at about 50 treatment hours, or at about 150 treatment hours, or at about 200 treatment hours, etc. Variations in the composition of the coating grown or deposited on the heater support and / or other components may result in many different plasma resistance or erosion rate values. Furthermore, a coating having a single composition but exposed to various plasmas may have many different plasma resistance or erosion rate values. For example, a plasma resistant material may have a first plasma resistance or erosion rate associated with a first type of plasma and a second plasma resistance or erosion rate associated with a second type of plasma.
[0037] Figure 2A illustrates one embodiment of a deposition process 200 by an ALD technique to grow or deposit a coating on an article (e.g., a heater support, an entire heater assembly, a portion of an electrostatic chuck, etc.). Figure 2B illustrates one embodiment of a deposition process 201 by an ALD technique, where the ALD technique grows or deposits a multi-layer plasma-resistant coating on an article. Figure 2C illustrates another embodiment of a deposition process 202 by an ALD technique described herein.
[0038] There are many different types of ALD processes, and the particular type can be selected based on several factors, including the surface to be coated, the coating material, and the chemical interactions between the surface and the coating material. The general principle of the various ALD processes involves the growth of a thin film layer by repeatedly exposing the surface to be coated to pulses of gaseous chemical precursors, where the precursors chemically react with the surface one at a time in a self-limiting manner.
[0039] 2A-2C show an article 210 having a surface. The article 210 may represent various materials of semiconductor processing chamber components, including but not limited to high temperature heater supports and / or the entire surface of a heater assembly in a processing chamber. The article 210 may be made of materials including AlN, dielectrics such as ceramics, metal-ceramic composites (e.g., Al2O3 / SiO2, Al2O3 / MgO / SiO2, SiC, Si3N4, AlN / SiO2, etc.), metals (aluminum, stainless steel, etc.), graphite, or other suitable materials, and may further include materials such as AlN, Si, SiC, Al2O3, SiO2, etc. In one embodiment, the article 210 is a high temperature heater constructed from a heater material having a thermal conductivity of about 50 W / mK to about 300 W / mK, or about 100 W / mK to about 250 W / mK, or about 150 W / mK to about 200 W / mK, or about 180 W / mK. The heater material may also have a specific heat capacity of about 0.15 cal / g°C at 25°C to about 0.30 cal / g°C at 25°C, or about 0.20 cal / g°C at 25°C to about 0.25 cal / g°C at 25°C, or about 0.25 cal / g°C at 25°C. The heater material may also have a CTE of about 4.6 to about 5.7 μm / m°C. In one embodiment, the article 210 is a high temperature heater for a semiconductor processing chamber, for example, fabricated from an AlN ceramic material. Such materials react with the fluorine plasma (e.g., NF3) in the processing chamber during cleaning to form AlF3. AlF3 has a high vapor pressure, which causes this reactant to sublime and deposit on other components in the chamber. During subsequent processing steps, the deposited AlF3 can flake, delaminate, or otherwise detach from other chamber components, contaminating the wafers there with particles.
[0040] In the case of ALD, both the adsorption of the precursor to the surface and the reaction of the adsorbed precursor with a reactant may be referred to as a "half-reaction". During the first half-reaction, the precursor is pulsed to the surface of the article 210 for a period of time sufficient for the precursor to be fully adsorbed on the surface. The adsorption is self-limiting since the precursor is adsorbed on a finite number of available sites on the surface to form a uniform and continuous adsorbed layer on the surface. Sites where a precursor has already been adsorbed are not available for further adsorption of the same precursor unless and / or until the adsorbed sites are subjected to a treatment that forms new available sites on a uniform and continuous coating. Typical such treatments are plasma treatments, treatments by exposing the uniform and continuous adsorbed layer to radicals, or the introduction of a different precursor that can react with the last uniform and continuous layer adsorbed on the surface.
[0041] In some embodiments, two or more precursors are injected together and adsorbed onto the surface of the article 210. Excess precursor is evacuated, and then an oxygen-containing reactant (or a fluorine-containing reactant) is injected to react with the adsorbate and form a constituent layer (e.g., of Y2O3-Al2O3). This new layer is available for adsorption of precursors in the next cycle.
[0042] 2A, the article 210 may be introduced to a first precursor 260 for a first period of time until the surface of the article 210 is fully adsorbed with the first precursor 260 to form an adsorbed layer 214. The article 210 may then be introduced to a first reactant 265 to react with the adsorbed layer 214 and grow a solid layer 216 (e.g., to fully grow or deposit layer 216, where the terms growing and depositing may be used interchangeably herein). For a monolayer coating, the first precursor 260 may be Y2O3, YF3, or Y x O y F zThe first reactant 265 may be a precursor for a rare earth metal-containing material such as Cr, H, or Al. Examples of precursors include yttrium precursors, zirconium precursors, erbium precursors, and the like. If an adhesion layer is used, the first precursor 260 may be an Al-containing precursor in some embodiments. If the layer 216 is an oxide, the first reactant 265 may be oxygen, water vapor, ozone, oxygen radicals, or another oxygen source. If the layer 216 includes AlN, the first reactant 265 may be, for example, NH3 nitrogen radicals, or another nitrogen source. If the layer 216 is a fluoride, a fluorine-containing reactant may be used. Thus, ALD may be used to form the layer 216. The layer 216 may be a single layer coating, or may be one layer (i.e., an adhesion layer) of a multi-layer coating.
[0043] In one embodiment where layer 216 is an AlN adhesion layer, article 210 (e.g., the surface of a high temperature heater) may be subjected to a first precursor 260 (e.g., a trimethylaluminum or TMA precursor) for a first period of time until all reaction sites on the surface of the article are consumed. The remaining first precursor 260 is evacuated, after which a first reactant 265 of NH3 is injected into the reactor to begin a second half-cycle. After the NH3 molecules react with the Al-containing adlayer produced in the first half-reaction, a layer of AlN 216 is formed.
[0044] Layer 216 can be uniform, continuous, and conformal. Layer 216 is free of pores (e.g., has zero porosity) or, in embodiments, has near zero porosity (e.g., 0% to 0.01% porosity). In some embodiments, after one ALD deposition cycle, layer 216 can have a thickness of less than one atomic layer to a few atoms. Some organometallic precursor molecules are large. After reacting with reactant 265, the large organic ligands may no longer exist, leaving much smaller metal atoms. One complete ALD cycle (e.g., including introduction of precursor 260 followed by introduction of reactant 265) can form a layer with an average thickness of less than one unit cell. For example, the growth rate of an AlN monolayer grown with TMA and NH3 is typically about 1.0 Å / cycle, while the AlN lattice constants are a=3.111 Å and c=4.981 Å (for a hexagonal structure).
[0045] Multiple full ALD deposition cycles may be performed to deposit thicker layer 216. Each full cycle (e.g., including introduction of precursor 260, exhaust, introduction of reactant 265, and exhaust again) adds an additional one to several atoms to the thickness. As shown, up to n full cycles may be performed to grow layer 216, where n is an integer value greater than 1. In embodiments, layer 216 may have a thickness of about 5 nm to about 10 μm, or about 25 nm to about 5 μm, or about 50 nm to about 500 nm, or about 75 nm to about 200 nm. In some embodiments, the coating may have a thickness of about 50 nm, or about 75 nm, or about 100 nm, or about 125 nm, or about 150 nm. If layer 216 is an adhesion layer, the adhesion layer may have a thickness of about 1 nm to about 50 nm, or about 2 nm to about 25 nm, or about 5 nm to about 10 nm. In certain embodiments, the thickness of the adhesion layer is about 1 nm, or about 5 nm, or about 10 nm, or about 15 nm.
[0046] When layer 216 is a coating including one or more rare earth metal-containing materials, layer 216 provides strong plasma resistance and mechanical properties without significantly affecting the thermal and electrical properties of the heater. Layer 216 may protect the components from erosion, enhance or maintain dielectric strength, and resist cracking at temperatures up to about 500° C., or up to about 550° C., or from about 500° C. to about 550° C. When layer 216 is an adhesion layer, it may improve adhesion of the rare earth metal-containing layer (or stack layers) to the components and prevent cracking of the coating at temperatures up to about 650° C.
[0047] FIG. 2B illustrates a deposition process 201 including deposition of layer 216 as an adhesion or barrier layer, as described with reference to FIG. 2A. However, deposition process 201 of FIG. 2B further includes deposition of additional layer 220 to form a multi-layer plasma-resistant coating. Thus, after layer 216 is completed, article 210 having layer 216 may be introduced to additional one or more precursors 270 for a second period of time until layer 216 is fully adsorbed with one or more additional precursors 270 to form adsorbed layer 218. Article 210 may then be introduced to reactant 275 to react with adsorbed layer 218 to grow solid rare earth metal-containing oxide layer 220 (e.g., to fully grow or deposit second layer 220). This solid rare earth metal-containing oxide layer 220 is also referred to as second layer 220 for simplicity. In this embodiment, layer 216 may be an adhesion or barrier layer comprising AlN. Thus, second layer 220 is grown or deposited entirely over layer 216 using ALD. In one example, precursor 270 may be a yttrium-containing precursor used in the first half-cycle and reactant 275 may be HO used in the second half-cycle.
[0048] The second layer 220 may form an yttrium-containing oxide layer or other rare earth metal-containing oxide layer. The layer may be uniform, continuous, and conformal. The porosity of the second layer 220 may be very low, less than 1% in embodiments, less than 0.1% in further embodiments, and about 0% in embodiments, or may be non-porous in further embodiments. The second layer 220 may have a thickness of less than one atom to a few atoms (e.g., 2-3 atoms) after one full ALD deposition cycle. Multiple ALD deposition steps may be performed to deposit a thicker second layer 220, with each step increasing the thickness by an additional one to a few atoms. As shown, the second layer 220 may have a target thickness by repeating the full deposition cycle m times, where m is an integer value greater than 1. In embodiments, the second layer 220 may have a thickness of about 5 ALD cycles (e.g., about 0.9 Å / cycle and two half reactions) to about 5 μm. If the second layer 220 is the first layer of a stack of layers, it may have a thickness from about 5 ALD cycles to about 500 nm, or from about 6 ALD cycles to about 250 nm, or from about 7 ALD cycles to about 100 nm, or from about 8 ALD cycles to about 50 nm. In embodiments, the thickness of the second layer 220 of the stack is from about 5 to about 15 ALD cycles, or from about 6 to about 14 ALD cycles, or from about 7 to about 13 ALD cycles, or from about 8 to about 10 ALD cycles.
[0049] The ratio of the thickness of the second layer 220 to the thickness of the layer 216 may be from 200:1 to 1:200. A higher ratio of the thickness of the second layer 220 to the thickness of the layer 216 (e.g., 200:1, 100:1, 50:1, 20:1, 10:1, 5:1, 2:1, etc.) provides better corrosion and erosion resistance, whereas a lower ratio of the thickness of the second layer 220 to the thickness of the layer 216 (e.g., 1:2, 1:5, 1:10, 1:20, 1:50, 1:100, 1:200) provides better heat resistance (e.g., improved resistance to cracking and / or delamination caused by thermal cycling).
[0050] The second layer 220 may be any of the rare earth metal-containing oxide layers discussed herein. For example, the second layer 220 may be Y2O3, YF3, or Y x O y F z In some embodiments, second layer 220 is a single-phase material formed from a mixture of at least two rare earth metal-containing precursors co-deposited by ALD (e.g., a combination of one or more of Y2O3, Er2O3, and Al2O3). For example, second layer 220 can be a single-phase material formed from a mixture of at least two rare earth metal-containing precursors co-deposited by ALD (e.g., a combination of one or more of Y2O3, Er2O3, and Al2O3). x Er y O z Or Y x Al y O z In one embodiment, the layer 216 is amorphous AlN and the second layer 220 is a polycrystalline or amorphous yttrium-containing oxide compound (e.g., Y2O3, Y x Al y O z , Y x Er y O z , etc.), alone or in a single phase with one or more other rare earth metal-containing materials. In another embodiment, article 210 is a graphite article, layer 216 is amorphous carbon, and second layer 220 is a polycrystalline or amorphous yttrium-containing compound (e.g., Y2O3, YZrO, YF3, Y x Al y O z , Y x Er y O z Layer 216 not only promotes adhesion, but may also function as a stress relief layer that is deposited prior to deposition of the yttrium-containing oxide layer.
[0051] In some embodiments, the second layer 220 can include Er2O3, Y2O3, or Al2O3. x Al y O z (For example, Er3Al5O 12 ), Y x Al y Oz , Y x Er y O z Or Er a Y x Al y O z (e.g., a single-phase solid solution of Y2O3, Al2O3, and Er2O3).
[0052] In some embodiments, the thickness of layer 216 may be about 1 nm to about 50 nm, or about 2 nm to about 25 nm, or about 5 nm to about 10 nm. In particular embodiments, the thickness of layer 216 is about 1 nm, or about 5 nm, or about 10 nm, or about 15 nm. The thickness of the rare earth metal-containing layer may be about 5 nm to about 10 μm, or about 25 nm to about 5 μm, or about 50 nm to about 500 nm, or about 75 nm to about 200 nm. In some embodiments, the thickness of second layer 220 may be about 50 nm, or about 75 nm, or about 100 nm, or about 125 nm, or about 150 nm. In particular embodiments, the total thickness of the coating including layer 216 and second layer 220 may be about 50 nm, or about 75 nm, or about 100 nm, or about 125 nm, or about 150 nm.
[0053] See FIG. 2C. In some embodiments, the multilayer coating includes three or more layers. Specifically, the coating may include a stack including a series of alternating layers of another material (e.g., AlN, ZrO, Y2O3, or other compounds disclosed herein) and a rare earth metal-containing oxide layer, or may include a series of alternating layers of layer 216 and a rare earth metal-containing oxide layer. In some embodiments, the rare earth metal-containing oxide layer is a layer of alternating sublayers. For example, the rare earth metal-containing oxide layer may be a series of alternating sublayers of Y2O3 and AlN, a series of alternating sublayers of Y2O3 and ZrO2, or a series of alternating sublayers of Y2O3 and Al2O3.
[0054] 2C, the article 210 having the layer 216 may be inserted into a deposition chamber. The layer 216 may be formed as described with reference to FIG. 2A or FIG. 2B. The article 210 may be introduced to one or more precursors 280 including one or more rare earth metal-containing materials for a period of time until the layer 216 is fully adsorbed with the one or more precursors 280 to form the layer 222. The article 210 may then be introduced to a reactant 282 to react with the layer 222 and grow the layer 224. Thus, the rare earth metal-containing layer 224 is fully grown or deposited on the layer 216 using ALD. In one embodiment, the precursor 280 may be a yttrium-containing precursor used in a first half cycle and the reactant 282 may be H2O used in a second half cycle. The rare earth metal-containing layer 224 may be a first oxide of Y2O3, Er2O3, ZrO2, or another oxide.
[0055] Article 210 having layer 216 and metal oxide layer 224 may be introduced to one or more precursors 284 for a period of time until layer 224 is fully adsorbed with one or more precursors 284 to form layer 226. Article 210 may then be introduced to a reactant 286 to react with layer 226 and grow additional layer 228. Thus, additional layer 228 (which may be the same material as layer 224) is grown or deposited entirely on rare earth metal-containing layer 224 using ALD.
[0056] As shown, the deposition of the rare earth metal-containing layer 224 and the aluminum oxide layer 228 may be repeated n times to form a stack of alternating layers 237, where n is an integer value greater than 2. n represents a finite number of layers selected based on the target thickness and properties. The stack of alternating layers 237 may be viewed as a rare earth metal-containing oxide layer including multiple alternating sublayers. Thus, the precursor 280, reactant 284, precursor 284, and reactant 286 may be introduced repeatedly in a sequential manner to grow or deposit additional alternating layers 230, 232, 234, 236, etc. Each of the layers 224, 224, 230, 232, 234, 236, etc. may be a very thin layer having an average thickness of less than a single atomic layer to a few atomic layers.
[0057] The alternating layers 224-236 described above have a 1:1 ratio. Here, there is a single layer of the first metal oxide for each interspersed layer. However, in other embodiments, there may be different ratios between the different types of layers, such as 2:1, 3:1, 4:1, etc. For example, in one embodiment, two Y2O3 layers may be deposited for each interspersed layer of different materials. Furthermore, the stack 237 of the alternating layers 224-236 has been described as an alternating sequence of two metal layers. However, in other embodiments, three or more metal layers may be deposited in the alternating stack 237. For example, the stack 237 may include three different alternating layers.
[0058] After the stack of alternating layers 237 is formed, an annealing process may be performed to cause the alternating layers of different materials to interdiffuse with each other to form a complex oxide having a single phase or multiple phases. Thus, after the annealing process, the stack of alternating layers 237 may become a single rare earth metal-containing oxide layer 238. For example, if the layers in the stack are Y2O3 and Al2O3, the resulting rare earth metal-containing oxide layer 238 may be Y3Al5O 12 (YAG) phase.
[0059] Each layer of rare earth metal-containing material may have a thickness of about 5-10 angstroms and may be formed by performing about 1 to about 10 cycles of the ALD process, where each cycle forms a nanolayer (or slightly smaller or larger than a nanolayer) of rare earth metal-containing material. In one embodiment, each layer of rare earth metal-containing oxide is formed using about 6 to about 8 ALD cycles. Each interspersed layer may be formed in about 1 to about 2 ALD cycles (or several ALD cycles) and may have a thickness of less than one atom to a few atoms. The layers of rare earth metal-containing material may each have a thickness of about 5 to 100 angstroms, and the layers of second oxide may each have a thickness of about 1 to 20 angstroms in embodiments, and 1 to 4 angstroms in further embodiments. The stack of alternating layers 237 may have a total thickness of about 5 nm to about 3 μm. The thin interspersed layers between the layers of rare earth metal-containing material may prevent crystal formation in the rare earth metal-containing layer. This allows an amorphous yttria layer to grow.
[0060] In the embodiments described with reference to FIGS. 2A-2C, the surface reactions (e.g., half-reactions) are performed sequentially, and in embodiments, the various precursors and reactants are not in contact. Before introducing new precursors or reactants, the chamber in which the ALD process is performed may be purged with an inert carrier gas (such as nitrogen or air) to remove any unreacted precursors and / or surface precursor reaction by-products. The precursors may be different for each layer, and the second precursor for the yttrium-containing oxide layer or other rare earth metal-containing oxide layer may be a mixture of two rare earth metal-containing precursors to promote codeposition of these compounds to form a single-phase material layer. In some embodiments, at least two precursors are used, in other embodiments, at least three precursors are used, and in further embodiments, at least four precursors are used.
[0061] ALD processes may be performed at a variety of temperatures depending on the type of process. The optimal temperature range for a particular ALD process is called the "ALD temperature window." Temperatures below the ALD temperature window may result in low growth rates and non-ALD type deposition. At temperatures above the ALD temperature window, reactions may occur via CVD mechanisms. The ALD temperature window may range from about 100°C to about 650°C. In some embodiments, the ALD temperature window is from about 20°C to about 200°C, or from about 25°C to about 150°C, or from about 100°C to about 120°C, or from about 20°C to 125°C.
[0062] ALD processing allows for uniform thickness conformal coatings on articles and surfaces with complex geometries, high aspect ratio holes (e.g., pores), and three-dimensional structures. By exposing each precursor to the surface for a sufficient amount of time, the precursors can disperse and react completely with the entire surface, including all of the three-dimensional complex features. The exposure time utilized to achieve conformal ALD on high aspect ratio structures is proportional to the square of the aspect ratio and can be predicted using modeling techniques. Additionally, ALD techniques are advantageous over other commonly used coating techniques because they allow for in-situ, on-demand material synthesis with specific compositions or formulations, and do not require lengthy and difficult fabrication of raw materials (such as powder feedstock or sintered targets). In some embodiments, ALD is used to coat articles with aspect ratios of about 3:1 to 300:1.
[0063] Using the ALD techniques described herein, Y x Al y O z (For example, Y3Al5O 12 ), Y x Er y O z , Y x Er y F z , or Y w Er x O y F zMulti-component films such as may be grown, deposited, or co-deposited using, for example, an appropriate mixture of precursors to grow a rare earth metal-containing oxide, either alone or in combination with one or more other oxides, which are described above and in more detail in the examples below.
[0064] In some embodiments, a wear-resistant layer including one or more rare earth metal-containing materials may be deposited over the stack layers. The wear-resistant layer may have a thickness of about 5 nm to about 5000 nm, about 5 nm to about 1000 nm, about 100 nm to about 5000 nm, or about 100 nm to about 500 nm.
[0065] Reference is now made to various high temperature components that may be coated with a rare earth metal-containing coating by ALD. FIG. 3 shows an exemplary susceptor 300 for an ALD chamber. The susceptor 300 has a protective coating (such as a rare earth metal-containing ceramic coating described herein). In one embodiment, the thin protective coating coats only the top surface of the susceptor. Alternatively, the thin protective coating coats the top and bottom surfaces of the susceptor. The thin protective layer may coat the sidewalls of the susceptor and the inner surface of the susceptor. The susceptor 300 may be used to simultaneously support and uniformly heat multiple wafers. The susceptor 300 may be radiantly heated using resistive heating elements or lamps. In one embodiment, the susceptor 300 includes a thermally conductive base such as graphite. The susceptor 300 may have a disk-like shape that may be large enough to support multiple substrates (e.g., multiple wafers). In one embodiment, the diameter of the susceptor is greater than one meter.
[0066] The susceptor 300 may include one or more recesses (also called pockets) 301-306. Each recess may be configured to support a wafer or other substrate during processing. In the illustrated embodiment, the susceptor 300 includes six recesses 301-306. However, other susceptors may have more or fewer recesses. Each of the recesses 301-306 includes various surface features. Example surface features of the recess 301 include an outer ring 308, a plurality of mesas 306, and channels or gas flow paths between the mesas 306. The features may have a height of about 10-80 micrometers in some embodiments.
[0067] The recesses 301-306 and surface features (e.g., mesa 306 and outer ring 308) may be fluidly coupled to a source of heat transfer (or backside) gas (e.g., He through holes drilled in the susceptor 300). During operation, backside gas can be supplied to the gas passages at a controlled pressure to enhance heat transfer between the susceptor 300 and the substrate.
[0068] The susceptor 300 may further include lift pin holes 310. For example, the susceptor 300 may include three lift pin holes that support lift pins (e.g., Al2O3 lift pins). The lift pins allow for loading and unloading of wafers onto the susceptor 300. The susceptor 300 may include recesses 315 that may be used to clamp the susceptor to a rotating spindle. The recesses 315 may include holes 320 that may be used to mechanically secure the susceptor 300 to the rotating spindle.
[0069] In some embodiments, the susceptor 300 may be formed from graphite and coated using ALD to form a rare earth metal-containing coating. An adhesion layer (such as a carbon layer deposited by CVD) may be formed on the susceptor 300 to promote adhesion of the rare earth metal-containing coating to the susceptor 300.
[0070] FIG. 4 illustrates coated components of a heater assembly 400 according to embodiments. The processing chamber 100 may be adapted to include the heater assembly 400. For example, the heater assembly 400 may be located under the showerhead 130 or lid in the internal volume 106 of the processing chamber 100. The heater assembly 400 includes a support 405 for holding a substrate (e.g., a wafer) during processing, the support 405 being attached to the end of an internal shaft 410. The internal shaft 410 may be located within the internal volume of the processing chamber 100. The internal shaft 410 may be attached to an external shaft 415 via a flange 420, which may be coupled to the chamber body 102 of the processing chamber 100 by a flange (not shown). The support 405 includes a mesa 406. The mesa is connected to electrical components (not shown) embedded within the heater material of the support 405. All surfaces that may be exposed to corrosive gases and plasma in the processing chamber are coated with a coating 425 (eg, a ceramic coating) according to embodiments described herein.
[0071] The support 405, shafts 410, 415, and flange 420 may be made from heater materials including AlN (e.g., AlN ceramic). In one embodiment, the support 405 may include metallic heater and sensor layers sandwiched between AlN ceramic layers. Such an assembly may be sintered in a high temperature furnace to create an integral assembly. The layers may include heater circuits, sensor elements, ground planes, radio frequency grids, and combinations of metal and ceramic flow channels. The heater assembly 400 may provide heater temperatures up to about 650° C. under vacuum conditions (e.g., from about 1 millitorr to about 5 torr).
[0072] The coating 425 may include one or more rare earth metal-containing oxide materials on the surface of the support 405 and / or on all surfaces of the heater assembly 400 that may be exposed to corrosive gases or plasmas in the processing chamber. The coating 425 may be a single layer coating or a multi-layer coating and generally has little or no effect on the thermal properties of the material of the support 405 or on the performance of the heater assembly 400. In some embodiments, the coating may have a thickness of about 5 nm to about 10 μm, or about 25 nm to about 5 μm, or about 50 nm to about 500 nm, or about 75 nm to about 200 nm. In some embodiments, the coating may have a thickness of about 50 nm, or about 75 nm, or about 100 nm, or about 125 nm, or about 150 nm.
[0073] 5 illustrates a cross-sectional side view of an exemplary component 500 having an internal channel formed therein, according to embodiments. The component 500 is representative of the top surface of a susceptor, heater, or electrostatic chuck, as previously described. For example, the component 500 may be a susceptor, and the overall diameter of the susceptor may be one meter. It should be understood that the features of the component 500 are not drawn to scale, and are merely intended to illustrate the internal channels of the component 500 and their connections.
[0074] In some embodiments, the body 502 of the component 500 may be formed from one or more materials. In some embodiments, the body 502 may be formed from a single material. Examples of materials are graphite, aluminum oxide, silicon carbide, metal oxides (such as ceramics or rare earth metal-containing ceramics).
[0075] The component 500 has multiple channels formed therein for gas flow. The channels may be used to create a vacuum or distribute gas. The channels include a central opening 508 through a bottom surface 506 of the component 500, a main opening 510 intersecting the central opening 508, a first cavity 518, a second cavity 522, a cavity conduit 520 connecting the first cavity 518 to the second cavity 522, and a chucking hole 516 along the top surface 504 of the component 500. In some embodiments, portions of the component 500 may be manufactured separately and bonded together to define the internal channels.
[0076] The main opening 510 provides a gas flow path between the central opening 508 and other channels, including other channels not shown, that may be formed in the component 500. In some embodiments, the main opening 510 passes at least partially or completely through the component 500. The main opening 510 may be formed using, for example, a gun drill. Plugs 512 are provided to seal the ends of the main opening 510.
[0077] The depth of the main opening 510 may range, for example, from about 0.3 meters to about 0.8 meters, and in some embodiments, may be about 0.5 meters. The diameter of the main opening 510 may range from about 3 mm to about 10 mm, and in some embodiments, may be about 6 mm. In some embodiments, the aspect ratio (depth:diameter) of the main opening 510 may range from 250:1 to 30:1, or any range between ratios where the first number is an integer and the second number is 1 (e.g., 200:1 to 40:1, 100:1 to 70:1, etc.).
[0078] The depth of the central opening 508 from the lower surface 506 to the inner inner surface 514 may range, for example, from about 15 mm to about 22 mm, and in certain embodiments, may be about 18 mm. The diameter of the central opening 508 may range, for example, from about 2 mm to 5 mm, and in certain embodiments, may be about 3 mm. In certain embodiments, the aspect ratio of the central opening may range from 22:1 to 4:1, or any range between ratios where the first number is an integer and the second number is 1 (e.g., 18:1 to 6:1, 10:1 to 5:1, etc.).
[0079] In some embodiments, the first cavity 518 and the second cavity 522 are connected by a cavity conduit 520. The cavity conduit is distributed to allow for an even gas flow through the chucking holes 516. In some embodiments, the chucking holes 516 may be used to provide a vacuum to secure the wafer to the top surface 504 of the component 500. In some embodiments, the length of each of the first cavity 518 or the second cavity 522 may range from about 50 mm to about 100 mm, and in certain embodiments, may be about 75 mm. The diameter of each of the first cavity 518 or the second cavity 522 may range, for example, from about 2 mm to 6 mm, and in certain embodiments, may be about 3 mm. In certain embodiments, the aspect ratio of the central opening may range from 50:1 to 8:1, or any range between ratios where the first number is an integer and the second number is 1 (e.g., 50:1 to 10:1, 30:1 to 20:1, etc.). In some embodiments, the diameter of the chucking hole 516 and the hollow conduit 520 may each range from about 0.5 mm to about 3 mm, about 0.5 mm to 1 mm, about 1 mm to about 3 mm, or about 1 mm to about 1.5 mm.
[0080] During use in plasma processing, the component 500 is exposed to a plasma for which a plasma-resistant coating (e.g., a ceramic coating as described herein) is beneficial. The internal channels of the component 500 are also likely to be exposed to the plasma, so it is beneficial to coat their interior surfaces 514. For example, coating 530 is shown coating the top surface 504 and bottom surface 506 of the component 500. To coat the interior surfaces 514 that are difficult to reach by line-of-sight deposition processes, coating 530 may be deposited using an ALD process, as described herein.
[0081] Figure 6A shows a cross-sectional view of a coated article 600 having a single coating 604 coated on article 602. Similarly, Figure 6B shows a cross-sectional view of a coated article 650 having multiple layers coated on article 652. Articles 602 and 652 may represent any of the articles / components described herein and may be formed from a suitable material, such as AlN, Al2O3, graphite, or rare earth metal-containing ceramics.
[0082] The coating 604 may be an ALD coating including any of the rare earth metal-containing ceramics discussed herein. For example, the coating 604 may be an ALD Y2O3 coating and the article 602 may be formed from AlN.
[0083] Coatings 654 and 656 may be formed from the same or different materials. In some embodiments, one or more of coatings 654 and 656 may include a rare earth metal-containing ceramic. In some embodiments, additional coatings may be formed. In some embodiments, coating 654 may be an adhesion layer that promotes adhesion between article 652 and coating 656. For example, coating 654 may be a CVD carbon bonding layer including amorphous carbon formed by CVD, coating 656 may be an ALD Y2O3 coating or another ALD rare earth oxide coating, and article 652 may be formed from graphite (e.g., crystalline or semi-crystalline graphite). The carbon bonding layer may be a pyrolytic carbon bonding layer. This pyrolytic carbon bonding layer may promote bonding of the ALD rare earth oxide coating. As another example, coating 654 may be an ALD Al2O3 coating, coating 656 may be an ALD Y2O3 coating, and article 652 may be formed from AlN.
[0084] In some embodiments, each of the articles 602 and 652 may have a different CTE than its respective coating. The greater the mismatch in CTE between two adjacent materials, the greater the likelihood that one of the materials will eventually crack, delaminate, or lose its bond to the other material. In some embodiments, the coating 604 may be formed to minimize the CTE mismatch between the coating 604 and the article 602, for example, so that the difference between the two CTEs is within 10% of the CTE of the article 602. This may be accomplished by varying the ratio of rare earth metal-containing compounds present in the coating 604, as described in more detail with respect to FIG. 7.
[0085] 7 illustrates a method 700 for forming a ceramic coating using atomic layer deposition, according to embodiments. Method 700 may be used to coat any of the articles / components described herein.
[0086] The method 700 begins at block 710, where an article is provided. The article may be any of the articles / components described herein (e.g., high temperature heater, electrostatic chuck, susceptor, etc.). The article may be formed from one or more materials (e.g., AlN, Al2O3, graphite, etc.). The article may be, for example, the component represented as article 210 in FIGS. 2A-2C. In one embodiment, the article may be a heater, electrostatic chuck, nozzle, gas distribution plate, showerhead, electrostatic chuck component, chamber wall, liner, liner kit, gas line, lid, chamber lid, nozzle, shingle ring, process kit ring, base, shield, plasma screen, flow equalizer, cooling base, chamber viewport, bellows, faceplate, or selectivity modulator. In another embodiment, the article is a high temperature susceptor (e.g., as represented by susceptor 300 in FIG. 3). In another embodiment, the article is a high temperature heater (e.g., as represented by heater assembly 400 in FIG. 4). In another embodiment, the article is an electrostatic chuck (e.g., as represented by ESC assembly 150 in FIG. 1).
[0087] At block 720, one or more rare earth metal-containing ceramic compounds are selected. The ceramic compounds include Y2O3, Y x Zr y O z , YZrOF, Y3Al5O 12 , Y4Al2O9, YF3, Y x O y F z , Er2O3, Er3Al5O 12 , ErF3, ZrO2, HfO2, E x O y F z , La2O3, Lu2O3, Sc2O3, ScF3, Sc x O y F z , Gd2O3, Sm2O3, and Dy2O3.
[0088] At optional block 730, two ceramic compounds are selected and a molar ratio between the two ceramic compounds is selected such that when a ceramic coating including the selected molar ratio of ceramic compounds is deposited on a surface of an article by atomic layer deposition, the result is a ceramic coating having a CTE within 10% of the first CTE of the article. By adjusting the ratio of the ceramic compounds, an ALD coating can be produced to substantially reduce or eliminate the CTE mismatch between the coating and the article.
[0089] Within the range of 40°C to 400°C, the CTEs of various ceramic compounds are as follows: Y2O3 is 7.2×10 -6 / ℃, ZrO2 is 10.5×10 -6 / ℃, and Al2O3 is 7.2×10 -6 / ℃, and AlN is 4.6×10 -6 / ℃, and 4×10 for SiC -6 / ℃, SiN is 2.8×10 -6 / ℃, La2O3 is 12.6×10 -6 / ℃, and Er2O3 is 6×10 -6 / ℃. The coating containing two compounds in different ratios was adjusted to a linear combination of the CTEs of the compounds, i.e., CTE coating =R A CTE A +R B CTE B , where R is the mole percent of a particular compound. For example, a 3:1 molar ratio of Y2O3 to ZrO2 is calculated as: 0.66 x 7.2 + 0.33 x 10.5 = 8.2 x 10 -6 / ℃.
[0090] In some embodiments, the first ceramic compound comprises a rare earth oxide and the second ceramic compound comprises a rare earth oxyfluoride or a rare earth fluoride. In some embodiments, the first ceramic compound comprises Y2O3 and the second ceramic compound comprises Y x O y F z Includes.
[0091] At block 740, ALD is performed (e.g., as described with respect to FIGS. 2A-2C) to deposit a ceramic compound, a combination of ceramic compounds, or a combination of two compounds in a selected ratio onto the article to produce a coated article. In some embodiments, additional coatings are deposited. For example, multiple layers of rare earth metal-containing compounds may be formed. In some embodiments, an adhesion layer is first deposited onto the article. This adhesion layer may be deposited by ALD, CVD, or other deposition methods (e.g., a CVD carbon layer).
[0092] In some embodiments, the compounds are deposited by ALD in alternating layers to achieve a selected ratio. For example, to achieve a 3:1 ratio of Y2O3 to ZrO2, three depositions of Y2O3 followed by one deposition of ZrO2 are alternating to achieve the desired thickness. In some embodiments, the compounds are co-deposited or deposited by co-adding precursors of the compounds (e.g., using a mixture of a first metal-containing precursor and a second metal-containing precursor).
[0093] The following examples are provided to aid in the understanding of the embodiments described herein and should not be construed as specifically limiting the embodiments described and claimed herein. Such variations, including the substitution of all equivalents now known or later developed within the knowledge of a person skilled in the art, and changes in the scheme or minor changes in experimental design should be considered within the scope of the embodiments incorporated herein. These examples can be achieved by carrying out the method 700 described above.
[0094] The coated article may further include a ceramic coating (e.g., a rare earth metal-containing coating). In one embodiment, the composition of the coating is Y2O3, Y x Zr y O z , YZrOF, Y3Al5O 12 , Y4Al2O9, ZrO2, YF3, Y x O y F z, Er2O3, Er3Al5O 12 , ErF3, E x O y F z , La2O3, Lu2O3, Sc2O3, ScF3, Sc x O y F z , Gd2O3, GdF3, Gd x O y F z , Sm2O3, Dy2O3, or a combination thereof. In one embodiment, the coating may be deposited using ALD (e.g., as described with respect to Figures 4A-2C).
[0095] The coated article may further comprise an adhesion layer between the component and the coating layer, hi one embodiment, the adhesion layer is an amorphous carbon layer.
[0096] In one exemplary embodiment, a 2 μm thick ALD coating of polycrystalline Y2O3 is formed on an AlN substrate.
[0097] In another exemplary embodiment, a 50 nm thick ALD coating of polycrystalline YZrO is formed on an Al2O3 substrate.
[0098] In another exemplary embodiment, a 160 nm thick ALD coating of polycrystalline YF3 is formed on an AlN substrate.
[0099] In another exemplary embodiment, an ALD coating of Y2O3, YZrO, or YF3 is formed on an Al2O3 buffer layer formed on an AlN substrate. The Al2O3 buffer layer may prevent a reactive interface layer from forming between the rare earth metal-containing coating and the AlN substrate.
[0100] In another exemplary embodiment, an ALD coating of crystalline Y2O3 is formed on an adhesion layer. The adhesion layer is formed on a crystalline graphite substrate. The adhesion layer may be an amorphous carbon layer deposited by CVD. The amorphous carbon layer promotes bonding between the crystalline graphite and the Y2O3. This exemplary embodiment is illustrated in FIG. 8, which shows a transmission electron microscope image of the graphite substrate on which the adhesion layer and ceramic layer are formed.
[0101] This particular embodiment of using a conformal coating of rare earth metal-containing ceramic on a graphite article with a carbon layer disposed therebetween is advantageous over other types of intermediate layers, such as a SiC layer. Graphite is relatively inexpensive, has high thermal conductivity, and is highly resistant to thermal shock, but is porous and contains impurities. Graphite is also easily eroded by fluorine-based plasmas, so it is beneficial to coat the graphite body to fill the pores and to provide a plasma-resistant layer to prevent contamination of the treated substrate by graphite impurities. Conformal plasma-resistant coatings as described herein are beneficial for coating graphite articles, but the porosity and roughness of the graphite surface can reduce the quality of the coating. Utilizing an amorphous carbon adhesion layer may improve adhesion between the ceramic layer and the substrate under high temperature operation, since the amorphous carbon adhesion layer is denser than the underlying sintered graphite substrate.
[0102] These aforementioned embodiments are not intended to be limiting, and are supplemented by other embodiments not expressly disclosed, which may be one of several combinations or permutations of the various embodiments described herein.
[0103] The above description provides numerous examples of specific systems, components, methods, and the like, and is specific and detailed, for the purpose of providing a good understanding of some embodiments of the present disclosure. However, it will be apparent to those skilled in the art that at least some embodiments of the present disclosure can be implemented without such specific and detailed descriptions. In other examples, well-known components or methods are not described in detail or are presented in a simple block diagram format to avoid unnecessarily obscuring the embodiments of the present disclosure. Therefore, the specific and detailed descriptions are merely exemplary. Particular embodiments may differ from these exemplary descriptions and still be considered to be within the scope of the present disclosure.
[0104] It should be noted that different references to "one" or "an" embodiment in this disclosure are not necessarily references to the same embodiment, and such references mean at least one. When "one embodiment" or "an embodiment" is mentioned throughout this specification, it means that a particular configuration, structure, or characteristic described in connection with that embodiment is included in at least one embodiment. Thus, the appearance of the phrase "in one embodiment" or "in an embodiment" in various places throughout this specification do not necessarily all refer to the same embodiment. Furthermore, the term "or" is intended to mean an inclusive "or" rather than an exclusive "or". When the term "about" or "approximately" is used herein, it is intended to mean that the nominal value presented is accurate to within ±1%.
[0105] Although the operations of the methods herein are shown and described in a particular order, the order of the operations of each method may be changed such that certain operations are performed in the reverse order or certain operations are performed at least partially in parallel with other operations. In another embodiment, instructions of different operations or sub-operations may be performed intermittently and / or alternatingly.
[0106] It should be understood that the above description is intended to be illustrative, and not limiting. Many other embodiments will be apparent to those skilled in the art upon reading and understanding the above description. Thus, the scope of the present disclosure should be determined based on the appended claims, along with the full scope of equivalents to which such claims are entitled.
Claims
1. 1. A coated article comprising:
1. An article suitable for use in a processing chamber, comprising: The exterior and an article comprising an internal channel including a surface that is difficult to reach for line-of-sight deposition processing; A coating formed on an exterior and interior surface of an article, comprising: Y 2 O 3 , Y x Zr y O z , YZrOF, Y 3 A 5 O 12 , Y 4 A 2 O 9 , Y.F. 3 , Y.O.F., Y. x O y F z , Er 2 O 3 , Er 3 A 5 O 12 , ErF 3 , Er x O y F z , La 2 O 3 , Lu 2 O 3 , Sc 2 O 3 , ScF 3 , Sc x O y F z , Gd 2 O 3 , GdF 3 , Gd x O y F z , Sm 2 O 3 , and Dy 2 O 3 and combinations thereof; and a coating which is substantially uniform, conformal and non-porous.
Citation Information
Patent Citations
Plasma corrosion-resistant thin film coating for high-temperature applications
JP2017514991A
Multi-layered plasma resistant coating by atomic layer deposition
JP2018150617A
Plasma-resistant coating of porous body by atomic layer deposition
JP2018162205A
Corrosion control for chamber parts
JP2018515691A
Non-Line of Sight Deposition of Erbium Based Plasma Resistant Ceramic Coating
US20180094348A1